ANALISIS ROA DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL PEMODERASIAN - Diana, Patrisia Fitri; Halim, Abdul; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2019)
This study aims to determine the effect of return on assets and leverage on firm value with an independent board of commissioners as a moderating variable. This type of research is an explanatory research with a quantitative approach. The population used in this study is banking companies listed on the Indonesia Stock Exchange in 2016-2017. The sampling technique in this study was purposive sampling so that the sample was selected as many as 34 companies with a number of research 68 companies in 2 years. The analysis technique of this research is the moderated regression analysis. The results of this study indicate that the independent board commissioner variable as a moderating variable is not proven to moderate, because the variable always has an abnormal distribution and multicollinearity occurs even though it has been transformed in SPSS. In order to continue this research, the independent board commissioner variable as a moderating variable was removed. The results showed that partially or t test return on assets was not significant no effect while partially or t test leverage variable had a significant negative effect on firm value